Photo-remediation of phenanthrene contaminated soil under visible light irradiation - Theerakarunwong C. (2017)
© 2016, Chiang Mai University. All rights reserved. The photocatalytic degradation of phenanthrene-contaminated soil over Fe-doped TiO 2 under visible light irradiation was investigated. The influence of physicochemical parameters such as catalyst dosage, dopant doping and soil pH was studied. The optimum amount of 3 at. wt%Fe doped TiO 2 (1%) expressed high photocatalytic activity of 83.45% under visible irradiation with alkaline conditions within 2 h. The Fe dopant significantly enhanced phenanthrene photocatalytic degradation by the strong oxidizing OH·radical and complex [Fe 3+ -ligand] could generated by the Photo-Fenton-Like catalyst reaction. A possible mechanism of phenanthrene degradation was proposed based on GC/MS elucidation. In the presence of Fe dopant, phenanthrene was degraded to heptadecane. Based on the quantification analysis, the presence of TiO 2 catalysts for degradation of phenanthrene in the soil sample could reduce the concentration of phenanthrene from 60 mg kg -1 to 20 mg kg -1 within 2 hours, while in the control soil without catalyst, the concentration of phenanthrene could only be reduced from 60 mg kg -1 to 40 mg kg -1 in equal time.